The Effectiveness of Meme Pictures To Teach Adjectives at SDN 2 Ringinpitu - Kusuma, Faris Nur; Nugrahini, Yulia (SALIENCE: English Language, Literature, and Education Journal, 2025)
This research aims to examine the effectiveness of using meme pictures as a teaching medium to enhance the mastery of adjectives among fifth-grade students at SDN Ringinpitu 2 during the 2024/2025 academic year. The study was motivated by classroom observations that revealed low student engagement and underachievement in English, particularly in understanding adjectives. Given the popularity of meme culture among children through social media, the study explored whether memes could serve as engaging and effective instructional media. A quantitative approach was used with a one-group pre-test and post-test experimental design involving 17 students. Data were collected using observation sheets, questionnaires, and adjective-based tests, then analyzed using SPSS version 27. The paired sample t-test results indicated a statistically significant improvement in students’ post-test scores compared to their pre-test results (p-value = 0.011 < 0.05). This finding confirms that the use of meme pictures has a positive and meaningful effect on students’ adjective mastery. The research concludes that integrating meme-based visual content into English instruction can be an effective and innovative strategy to improve student learning outcomes, particularly in vocabulary development.